Comparative constitutionalism in South Asia - Khilnani, Sunil, 1960-; Raghavan, Vikram; Thiruvengadam, Arun K. (Oxford : Oxford University Press, 2013)
This book seeks to fill a void in the representation of South Asian constitutions and constitutionalism in international discourse. Although parts of South Asia have remained obscure and unstable on the fine balance of constitutional stability and constitutionalism, an appreciable number of countries have successfully operated constitutional schemes that are based on systems developed in the West through a process of trial and error. In this volume, an array of experts studies the successes and failures of constitutionalism in this extremely diverse region.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Constitutional law -- South Asia